Biomarker counseling, disclosure of diagnosis, and follow‐up in patients with mild cognitive impairment: A European survey of EADC centers: Dementia care research (research projects; nonpharmacological) / Assessment and care planning. (7th December 2020) - Frederiksen, Kristian Steen; Nielsen, Rune; Robinson, David; Hausner, Lucrezia; Hanseeuw, Bernard J; Nobili, Flavio Mariano; Rikkert, Marcel GM Olde; Hugon, Jacques; Andersen, Birgitte Bo; Mendonca, Alexandre; Traykov, Latchezar; Yener, Görsev; et al.
Abstract: Background: The concept of mild cognitive impairment (MCI) was developed as a research to capture a group of patients with objectively measurable cognitive impairment not fulfilling the criteria for dementia but has since diffused into clinical practice in many centers. The objective of the present survey was to assess practices with regards to diagnostic procedure and disclosure including biomarker counselling and management in patients with MCI. Methods: The present study was designed as an online survey of medical doctors working in European Alzheimer Disease Centers (EADC). Results: A total of 34 center coordinating doctors out of 41 (80.9 %) and 110 out of 213 (50.6 %) individual doctors responded to the survey. Almost all respondents had access to MRI (98.2%; n=108) and CSF sampling (91.8%; n=101), whereas fewer had access to 18F‐FDG‐PET (74.5%; n=82) and amyloid PET (50.9%; n=56). Most, but not all respondents, always or usually discussed the decision to order biomarkers with patients with MCI (85.7%; n=90) and dementia (81.1 %; n=86). Nearly half (49.5 % n=54) of respondents found that the diagnosis of MCI was meaningful to a great extent, whereas this was 75.5 % (n=84) for dementia (z=3.77; p=0.0002). Almost all respondents reported always or usually following up MCI (95.2%; n=100) and dementia patients (90.48%; n=95). Half (50.5%; n=53) of respondents reported following MCI patients for 5 or more years and for dementia 45.3% (n=48). Conclusion: We found that biomarkers are widely used in patients with MCI, but that not all patients receive adequate pre and post biomarker counselling. For a considerable proportion of practices, we found considerable variability across centers. This may indicate that clinicians lack guidance on issues related to diagnostic disclosure including biomarker sampling.